The Role and Responsibilities of Notaries as Members of the Notary Supervisory Council According to Law No. 30/2004 - Soetopo, Hadi (Universitas Ekasakti, 2024)
This study examines the role and duties of notaries serving as members of the Notary Supervisory Council (MPN) in accordance with Law No. 30/2004 on the Notary Position (UUJN). The goal of this study is to understand the role of notaries in the MPN framework and determine the duties and difficulties they face in upholding professionalism and honesty. This study employs a normative analysis methodology with a qualitative approach to investigate the execution of MPN responsibilities at various levels. We achieve this through a comprehensive evaluation of existing literature and the examination of case studies. The comprehensive analysis centres on the interaction between notaries and MPN, as well as their respective responsibilities in maintaining the code of ethics and resolving conflicts. The findings suggest that notaries have a pivotal role in the MPN framework, which comprises three tiers: MPD, MPW, and MPP. Notaries at every level have the responsibility of overseeing, promoting, and enforcing the code of ethics, as well as settling conflicts through mediation. According to the report, the functions and obligations of notaries in MPN are critical for upholding the profession's integrity and professionalism. MPN employs a hierarchical system of supervision to carry out its duties effectively and efficiently, ensuring that all notaries in Indonesia comply with legislation and maintain public confidence in the profession.